MODEL MICRO-MACRO LINK PENGEMBANGAN KEBIJAKAN PERIKANAN TANGKAP DI KABUPATEN BELITUNG - Dahlan, M. Nizar; Wiryawan, Budy; Murdiyanto, Bambang; Baskoro, Mulyono S.; Fauzi, A. (Jurnal Teknologi Perikanan dan Kelautan, 2017)
Bordered with the South China Sea, which has potential sustainable fishery resource equal to 1.06 million tones/year, Belitung still not employed fishery as income generating sectors for the regency. The aim of this research is to formulate strategic policies on the development of capture fisheries, thus fishery sector may serve as one economic basis for Belitung. Analysis used for this research was descriptive analysis and macro-micro linkage developed through structural equation modelling (SEM). Research results showed a significant influence between fisheries effort with fishing ground area (P = 0.008), between fiscal condition with market growth (P = 0,002) and fishing ground area (P = 0,005), between national policy with monetary tendency (P = 0,002) and fishing trade (P = 0,007), between fishing trade with regional economy (P = 0,003), and between regional economy with supporting sectors (P = 0,000). Therefore, the development policy for fishery sector should employ existing resource potential and spatial reference. Other viewpoint related with the security of local fishery market product and premium fishery basis whenever there is global economic and financial fault. Such condition applies to anticipate challenging economic situation and whenever applied national policy unsuitable for the local condition. Development of permanent trade routes is expected, as well as ensuring the continuation of services that support fishery development